(untitled) (Historia, 2021)
1652 - The beginning of colonialism in South Africa? The founding of the VOC refreshment station at the Cape in 1652 is often referred to as the beginning of a period of colonialism in South Africa which lasted until 1994. An examination of the definitions of colonialism which are used by historians today reveals that some scholars reserve the word colonialism for the system of Western domination of large parts of Africa and Asia during the nineteenth and twentieth centuries. There are, however, many historians today who use the term to describe various forms of domination in world history from the earliest times to the present. The article argues that only a broad definition of colonialism makes it possible to understand colonialism as a historical phenomenon. Various forms of colonialism are identified and their role in South African history over the last 2000 years is briefly discussed. The discussion focuses on the role of Dutch colonialism at the Cape within the broader context of the history of colonialism in South Africa. It is pointed out that colonialism during the VOC period differed in some essential respects from colonialism in South Africa during the nineteenth and twentieth centuries. During the Dutch period a process of integration between the colonisers and the colonised peoples took place, while in the later period processes of polarisation were dominantDaar word vandag dikwels na die stigting van die VOC-verversingspos aan die Kaap in 1652 verwys as die begindatum van ’n tydperk van kolonialisme in Suid-Afrika wat eers in 1994 tot ’n einde gekom het. As die definisies van kolonialisme wat vandag deur historici gebruik word, van nader bekyk word, blyk dit daar sommige skrywers is wat die term reserveer vir die vorm van Westerse oorheersing oor groot dele van Afrika en Asië gedurende die negentiende en twintigste eeue. Baie historici vandag gebruik die term kolonialisme in ’n veel wyer sin om verskeie vorme van beheer deur een groep oor ’n ander sedert die vroegste tye aan te dui. In hierdie artikel word geargumenteer dat slegs ’n ruim definisie van kolonialisme dit moontlik maak om kolonialisme as historiese verskynsel goed te begryp.